Investigating the Effectiveness of People\'s Knowledge, Attitude, and Practice Regarding the Acceptance of COVID-19 Vaccination: A Systematic Review - Amir Faghihi; Erfan Pourshahri; Mostafa Bijani (Mazandaran University of Medical Sciences, 2023)
Introduction and purpose: The COVID-19 pandemic is still one of the major challenges faced by health systems around the world. Knowledge, attitude, practice, and acceptance of the COVID-19 vaccine are important factors in encouraging people to inject the vaccine. This study was conducted to investigate the effectiveness of people's knowledge, attitude, and practice regarding the acceptance of the COVID-19 vaccination. Methods: This study was a systematic review based on articles published in 2019-2022 that examined the knowledge, attitude, practice, and acceptance of community members regarding the COVID-19 vaccine. A total of 14 databases and 56 articles were evaluated. Databases included Web of Science, Cochrane Library, PubMed, CINAHL, Google Scholar, Ovid, Science Direct, WILEY, Scopus, Pro-Quest, Medline, Elsevier, Magiran, and SID. Results: After analyzing the articles, abstracts, and main texts, 13 articles, all of which were descriptive-cross-sectional studies, were selected for the final analysis. It was found that 61.5% (n=8) of studies showed a high and acceptable level of knowledge, 30.7% (n=4) a high level of attitude, 15.3% (n=2) an average level of practice, and 23% (n=3) a high level of acceptance toward COVID-19 vaccine. Conclusion: People's level of knowledge about the COVID-19 vaccine was at a high level. Nevertheless, people's attitude towards the injection of the COVID-19 vaccine and its effectiveness, and consequently, the acceptance of this vaccine and the willingness to inject it was at a low level. Therefore, health system policymakers should take measures according to the cultural background of the societies to encourage people to inject the vaccine against COVID-19.